Assessment of antibacterial activity of fresh garlic juice extract against Vibrio spp. isolated from hybrid grouper (Epinephelus fuscoguttatus x Epinephelus lanceolatus): An in vitro study - Razali, Muhamad Izzuan; Nik Yusoff, Nik Haiha; Mohd Idris, Shaharah; Abdullah, Azila; Ramly, Rimatulhana; Mohammad Ridzuan, Mohd Syafiq; Mansor, Nur Nazifah; Mustafa, Sufian; Nawi, Mohd Firdaus (2022)
We assessed the antibacterial activity of fresh garlic juice extract against Vibrio spp. isolated from hybrid grouper (Epinephelus fuscoguttatus x Epinephelus lanceolatus). The disc diffusion method was conducted to evaluate five concentrations of fresh garlic juice extract against Vibrio alginolyticus, Vibrio vulnificus, and Vibrio parahaemolyticus. The tested concentrations are 20%, 40%, 60%, 80%, 100%, and oxytetracycline (OTC) antibiotic as a positive control, while absolute ethanol as a negative control. Results from the disc diffusion study revealed 100% and 80% garlic juice extract have higher inhibition zone against V. alginolyticus and V. vulnificus compared to OTC. The inhibition zone against V. parahaemolyticus was slightly less when 100% garlic juice extract gave an equal inhibition zone with OTC and smaller in other concentrations. Minimum inhibition concentration (MIC) and minimum bactericidal concentration (MBC) were also studied, which resulted in the lowest MIC value was V.alginolyticus (0.011%) followed by V.vulnificus (0.023%) and the highest is V. parahemolyticus (0.045%). Similarly, the lowest MBC value was V. alginolyticus (0.023%) followed by V. vulnificus (0.045%) and the highest is V.parahemolyticus (0.09%). The results revealed that fresh garlic juice extract was effective against the test bacteria and showed the potential of using fresh garlic juice extract treatment as an antibacterial agent to treat vibriosis in hybrid grouper fish.